Synthesis And Characterisation Of Microporous Alpo-5 Molecular Sieves Templated By Novel Imidazolium-Based Structural Directing Agents - Damien, Khoo Yiyuan (2013)
Microporous aluminophosphate (AlPO) molecular sieves have been successfully crystallised under hydrothermal and ionothermal syntheses. The former approach engaged 3-(2,3-dihydroxypropyl)-1,2-dimethylimidazolium hydroxide, [dhpdm]OH, as a new structure-directing agent (SDA). The ionothermal synthesis was carried out by using 1-ethyl-2,3-dimethylimidazolium bromide, [edmim]Br ionic liquid, as both solvent and structure-directing agent. Both methods were investigated by optimising the synthesis conditions such as crystallisation time and temperature and molar concentrations of SDA, P2O5/Al2O3 ratio and H2O in precursor gels. The results obtained showed different morphologies of well-defined AlPO-5 (AFI) crystals with AFI topology under different synthesis conditions. Hydrothermal treatment using [dhpdm]OH produced crystals with column-strip, aggregated hexagonal prism, hexagonal barrel and narrow cylindrical rod structures. On the other hand, ionothermal treatment using [edmim]Br ionic liquid yielded aggregated and spheroidal hexagonal thin-plate crystals.